Kutai, Tonggak Sejarah Nasional Indonesia - Gunadi Kasnowihardjo (Naditira Widya, 2007)
Kutai in Muara Kaman is acknowledged the oldest evidence of the ancient history of Indonesia. In order to present a complete understanding on its role, an extensive site exploration and excavation in Muara Kaman can be achieved by carrying out research collaboration between archaeology and history. In 1997, an archaeological research has been undertaken by Machi Suhadi, which was continued by Bambang Sulistyanto in 1998. However, the researches have not covered the whole area which is suggested as the ancient Kutai Kingdom. I presume that ancient Kutai has developed since prehistory and progressed until protohistory. Therefore, to study Kutai during that specific time range is very important. What occurred in the region considered ancient Kutai? Who visited ancient Kutai? Had trading activities taken place then? What was the main commodity?